16S rRNA Gene Amplicon Sequence Data from Chicken Cecal Feces from Vietnam and Thailand - Takeshita, Nachiko; Kim, Hyunjung; Witoonsatian, Kringkrai; Tohya, Mari; Võ, Tấn Hùng; Boonyong, Nuchjaree; Nguyễn, Thị Phương Bình; Nakagawa, Ichiro; Meekhanon, Nattakan; Nguyễn, Ngọc Hải; Sekizaki, Tsutomu (Microbiology resource announcements, 2019)
Here, we report 16S rRNA amplicon sequence data from chicken cecal feces from Vietnam and Thailand. Lachnospiraceae , Ruminococcaceae , and Bacteroidaceae were dominant in cecal feces microbiota. Here, we report 16S rRNA amplicon sequence data from chicken cecal feces from Vietnam and Thailand. Lachnospiraceae , Ruminococcaceae , and Bacteroidaceae were dominant in cecal feces microbiota.